Penyusunan Bahan Ajar Digital Akuntansi Keuangan Kelas XI Semester 2 Pada SMK Kartini Batam - Anita Anita; Nini Cartina (Universitas Internasional Batam, 2021)
In the process of compiling digital teaching materials, the material explanation is adjusted to the syllabus provided by the school. Online media was often used as a learning activity before the Covid-19 pandemic. The discussion of the material is explained by the actual associated events where students can more easily learn the summary that has been designed on each material in the syllabus. Learning activities of students are very important in terms of assessment, the entry of graduates (freshgraduate) into the world of work is a problem for companies to recruit so that there are many unemployed people. Data collection techniques are using online media such as ebooks and the internet. The problem we face when evaluating teaching material data is the absence of partner responses to teaching materials that are ready to be sent. Online learning activities at home accompanied by teaching materials are very efficient where students can gain knowledge when facing a pandemic or review the material. In the future, digital technology is very useful, it is recommended for each school to be able to make a summary of the syllabus material related to the problems of the world of work.